2019
DOI: 10.1097/md.0000000000017143
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of urinary microRNA in patients with chronic hepatitis B

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Interestingly, miRNAs associated with EVs can also be biomarkers for diseases other than cancer. miRNAs from EVs can be used for the detection of acute myocardial infarction 46 , 47 , chronic hepatitis B 48 , and their correlation with the presence of liver toxicity has been demonstrated in rat models 49 . Despite the obvious advantages of using EVs for disease detection, the small sample size and difficulty of separation are still the limiting factors for widespread use 50 , 51 .…”
Section: Components Of Urine Biopsymentioning
confidence: 99%
“…Interestingly, miRNAs associated with EVs can also be biomarkers for diseases other than cancer. miRNAs from EVs can be used for the detection of acute myocardial infarction 46 , 47 , chronic hepatitis B 48 , and their correlation with the presence of liver toxicity has been demonstrated in rat models 49 . Despite the obvious advantages of using EVs for disease detection, the small sample size and difficulty of separation are still the limiting factors for widespread use 50 , 51 .…”
Section: Components Of Urine Biopsymentioning
confidence: 99%
“…[7] miRNAs play an important role in the progression of hepatitis B and HBV-related liver fibrosis and can be used as potential biomarkers. [8] Zhang et al [9] found that the serum levels of miR-122, miR-572, miR-575, miR-638, and miR-744 were dysregulated in patients with chronic hepatitis B or nonalcoholic steatohepatitis. The levels of these miRNAs may serve as biomarkers of liver damage caused by chronic hepatitis B and nonalcoholic steatohepatitis.…”
Section: Introductionmentioning
confidence: 99%